Förutsättningar för egentligt ansvarsgenombrott trots HDs (icke-existerande) praxis - Feldtblad,Hannah (2020)
In Swedish case law, there have been cases where a court has imposed a personal liability on shareholders, so-called piercing the corporate veil, despite the principle of the shareholders' limited liability for the company's obligations in the 1st Chapter 3 § of the Swedish Companies Act, without explicit support in law. Six years ago, the Supreme court had the opportunity to decide in the question of piercing the corporate veil in NJA 2014 s. 877, but announced a verdict difficult to interpret. In the doctrine, the case is commonly interpreted as denying the future use of piercing the corporate veil, as a rule in association law, and its existence in general. The Supreme court’s verdict falls under the heading “particularly qualified cases”, a concept undefined and launched by them, which must be considered to encompass the traditional discussion of piercing the corporate veil that the Supreme court in the verdict has distanced itself from. To the question of there after NJA 2014 s. 877 being preconditions for a Swedish court to breach the shareholder’s limited responsibility for the company’s obligations according to unwritten principles attributable to association law, an affirmative answer is given. The conclusion that the Supreme court has left the issue of piercing the corporate veil to be decided in the future is also derived.
Keywords: Ansvarsgenombrott; NJA 2014 s. 877